2016
DOI: 10.1111/bcpt.12671
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Concentrations of Indocyanine Green Reflect Transfer Rates Across Membrane Transporters

Abstract: Perioperative imaging with indocyanine green (ICG) is developing to increase safety in dissecting anatomical structures during hepatobiliary surgery. Images obtained with the fluorescence camera rely on concentrations measured in liver regions of interest. However, how ICG sinusoidal uptake and hepatocyte elimination rates generate ICG hepatocyte concentrations is largely unknown. To investigate such issue and better understand the role of membrane transporters in generating ICG hepatocyte concentrations, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…ICG has been commonly used for assessment of liver function, especially hepatic blood flow in clinical. 22) ICG is transported by several transporters. It is reported that ICG enters through organic anion transporting polypeptides (OTAP1B1/3) and Na(+)/taurocholate cotransporter polypeptide (NTCP) expressed on the sinusoidal membrane of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICG has been commonly used for assessment of liver function, especially hepatic blood flow in clinical. 22) ICG is transported by several transporters. It is reported that ICG enters through organic anion transporting polypeptides (OTAP1B1/3) and Na(+)/taurocholate cotransporter polypeptide (NTCP) expressed on the sinusoidal membrane of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that ICG enters through organic anion transporting polypeptides (OTAP1B1/3) and Na(+)/taurocholate cotransporter polypeptide (NTCP) expressed on the sinusoidal membrane of hepatocytes. 23) Besides, it is also reported ICG elimination from hepatocytes is mainly due to efflux back to sinusoids, and biliary transport across the canalicular occurs across P-glycoprotein 2 (Mdr2). 24) In this study, ICG clearance from the plasma was delayed in the CKD group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The gamma counter placed over the liver detects the concentrations of both imaging compounds, avoiding the collection of serial liver biopsy samples. Indeed, serial biopsies alter the liver structure over the period of the protocol (Cusin et al, 2017). This improved experimental model directly measures the effects of RIF on fluxes across hepatocyte membranes and is a new tool for the understanding of transporter-mediated drugdrug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the ICG clearance test has certain limitations, as constant hemodynamic conditions (stable liver perfusion rate and hepatic blood flow) are required for liver function analysis 40 42 and, in cases of cholestasis and hyperbilirubinemia, carrier competition of bilirubin and ICG at the OATP1 transporter might occur 43 , 44 . It is also known that various drugs (e.g., rifampicin) exert inhibitory effects on the OATP pathway and might influence hepatocyte ICG uptake 45 , 46 . Similar to the findings of Tamada et al .…”
Section: Discussionmentioning
confidence: 99%